SAT0140 Recommendations for Investigating and Managing Comorbidity in Rheumatoid Arthritis. (10th June 2014) - Loza, E.; Lajas, C.; Andreu, J.L.; Balsa, A.; Gonzalez-Alvaro, I.; Illera, O.; Jover, J.A.; Mateo, I.; Orte, J.; Rivera, J.; Rodríguez Heredia, J.M.; Romero, F.; et al.
Abstract : Objectives: To develop evidence-based recommendations for the detection and management of comorbidity in rheumatoid arthritis (RA) in daily practice. Methods: We used a modified RAND/UCLA methodology and systematic review. Discussion groups established recommendations, which were prioritized, refined, and graded in a large group of users by a 2-round Delphi survey. Results: The first 9/21 recommendations with agreement (A), and level of evidence (LE) are listed in Table 1 . Conclusions: We established recommendations that cover what, how, when and by whom to investigate and manage comorbidity in RA. Additional materials, such as tables and checklists, will facilitate their implementation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3089